Implementation of Digital Governance at Sub-Branch Post Offices - Aldiniatul Islam; Desi Susanti; Fari Rahma; Miftahul Khairat; Sisri Nauratul Ilmi; Syamsir (PT FORMOSA CENDEKIA GLOBAL, 2023)
Delivery of goods that used to be usually done through the post office, now has serious competitors, namely private delivery service companies such as JNE, J&T Ekspress, SiCepat, Ninja Express, and so on. This study aims to explain how digital governance is implemented at the North Padang District post office. This study uses a qualitative method. The results of the study show that the Sub-Branch Post Office has implemented digital service governance. The application used by the post office is Pospay, and in its application there are several obstacles encountered such as network problems and there are still many ordinary people who do not understand the use of the Pospay application. So it can be concluded that the Pospay application is very useful for the community because with this application the community can pay various types of bills such as electricity bills, home and postpaid telephones, PDAM, vehicle installments, and so on.